Improving human capital to support ethnic minority families - Nguyen, Thi Duyen (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
This study analyses the current situation and solutions for supporting minority ethnic households in Thanh Hoa, Vietnam, in improving their sustainable poverty alleviation capacity, by interviewing 3,400 representatives from poor and poverty-alleviated households of six ethnic minorities (Thai, Tho, Muong, Hmong, Dao, and Khmu) in Thanh Hoa province. The statistical results describe the number of laborers in the households, the educational level of the head of the household, health capacity, skills, labor production experience of the households, capital mobilization capabilities for business, and proposed solutions for enhancing human capital to leverage sustainable poverty. Minority ethnic households need to participate in training and vocational programs to improve their educational level, knowledge, understanding, and skills to enhance their sustainable poverty alleviation capacity.
Keywords: človeški kapital; human capital; intersekcija; manjšinska gospodinstva; minority ethnic households; poverty alleviation capacity; sposobnost zmanjševanja revščine; Thanh Hoa